EXTENT OF UTILIZATION OF TEACHERS AS HUMAN RESOURCE IN SECONDARY SCHOOL ADMINISTRATION IN ENUGU STATE, NIGERIA (UNIZIK Journal of STM Education, 2023)
The study centered on the extent of utilization of teachers as human resource in secondary school administration in Enugu state. Two research questions guided the study while two null hypotheses were tested at 0.05 level of significance. Descriptive survey research design was adopted for the study. The population of this study comprise of all the teachers in the 314 public secondary schools in Enugu State. Available data show that there are 2282 male and 6601 female secondary school teachers in Enugu state. The sample size of this study2 was 889 made up of 229 male teachers and 660 female teachers. Questionnaire was designed to elicit appropriate information from the respondents. The reliability coefficient of the instrument was calculated using Cronbach Alpha method. Alpha value was found to be 0.93 indicating high reliability of the instrument. Mean score and standard deviation were used to answer the research questions, and t-test statistic was used to test the hypotheses at 0.05 level of significance. Some of the findings of the study indicated that there is great extent to which teachers are utilized in instructional planning. The findings also showed that there is great extent to which teachers are utilized in students’ personnel administration in secondary schools in Enugu state. Based on this, it was recommended among others that curricular planners should always involve teachers in planning and also integrate them to any curricular innovation.
Keywords: Utilization; Human Resource; School Administration